The Role of Village Apparatus, Human Resources, and Women's Empowerment in Improving the Living Standards in Tourist Villages of Serdang Bedagai Regency - Sinaga, Eryolen Ratno; Fahrizal Perangin Angin; Mangasi Sinurat; Fitrianingsih (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
The purpose of this study was to see how the active role of village officials, the quality of human resources (HR), and women's empowerment have an impact on improving the standard of living of the tourist village community in Serdang Bedagai Regency. Quantitative methods were used to collect data through questionnaires to 95 respondents. To analyze the data, the PLS-SEM (Partial Least Square Structural Equation Modeling) model was used. The results showed that only the variable of the active role of village officials had a significant impact on improving the standard of living of the community, and the quality of human resources and women's empowerment did not have a significant impact. This research model can explain 94.1% of the variables that affect a better standard of living. The results show that village officials must be actively involved in supporting the growth of tourist villages and community welfare. Recommendations focus on increasing the role of village officials and strategies to improve empowerment and quality of HR.